2018
DOI: 10.12809/ajgg-2017-276-oa
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute geriatric services for nursing home residents on emergency department presentation and hospitalisation

Abstract: Background. Prior to May 2015, our hospital provided only non-urgent geriatric services for nursing home residents. Thereafter, the Connecting Care Programme was introduced to provide acute geriatric services, including administration of intravenous antibiotics and fluids and a variety of other procedures. This audit aimed to investigate the impact of acute geriatric services for nursing home residents on emergency department presentation and hospitalisation. Methods. Medical records of nursing home residents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We demonstrated a 36.1% reduction in the risk of hospital admis- Previous feasibility studies of our acute service during the early days showed a 10.2% reduction in ED transfers from RACFs and an increased rate of discharge from ED for RACF residents (38.4% vs 52.5%, odds ratio=1.76, 95% CI 1.2-2.4, P <.001) compared to the SGOS period. 11,13 ITS analysis using unpublished data from those study periods found a statistically nonsignificant 26% reduction in the risk of admission from RACF. The statistically significant larger effect size in our current study could be explained by the fact that our service has matured over time, with a stronger referral base and a bigger sample size with adequate power.…”
Section: Discussionmentioning
confidence: 93%
“…We demonstrated a 36.1% reduction in the risk of hospital admis- Previous feasibility studies of our acute service during the early days showed a 10.2% reduction in ED transfers from RACFs and an increased rate of discharge from ED for RACF residents (38.4% vs 52.5%, odds ratio=1.76, 95% CI 1.2-2.4, P <.001) compared to the SGOS period. 11,13 ITS analysis using unpublished data from those study periods found a statistically nonsignificant 26% reduction in the risk of admission from RACF. The statistically significant larger effect size in our current study could be explained by the fact that our service has matured over time, with a stronger referral base and a bigger sample size with adequate power.…”
Section: Discussionmentioning
confidence: 93%
“…The authors reported mixed results for interventions involving geriatric assessment teams or outreach services. Results ranged from significantly decreased hospital admission rates ( Ling et al, 2018 ), decreased odds of hospital readmissions ( Hullick et al, 2021 ), increased odds of hospital admissions ( Hullick et al, 2016 ), and no significant effect on hospital admissions ( Cavalieri et al, 1993 ). Two studies reported cost savings by using fewer services, consults, and the use of skilled nursing staff rather than a physician-only approach ( Burl et al, 1998 ; Chan et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although no authors discussed if or how they explicitly and proactively contextualized the intervention they examined, several ( n = 6) discussed contextual factors that may have influenced study results. Examples include seasonal variation in ED transfers ( Chan et al, 2018 ; Ling et al, 2018 ); different understandings of RACF legislative guidelines ( Chhabra et al, 2012 ); differences in staff mix, availability, and expertise ( Burl et al, 1998 ; Chan et al, 2018 ); the ability to provide rapid responses in RACF ( Chan et al, 2018 ); availability of ambulance services, awareness of geriatric assessment teams or services ( Chan et al, 2018 ; Ling et al, 2018 ); and factors related to leadership, a culture that supports quality improvement and a community of practice ( Hullick et al, 2016 , 2021 ).…”
Section: Resultsmentioning
confidence: 99%